Computer simulations of water interactions with low-coordinated forsterite surface sites: Implications for the origin of water in the inner solar system - King, H.; Stimpfl, M.; Deymier, P.; Drake, M.; Catlow, C.; Putnis, Andrew; de Leeuw, N. (Elsevier BV, 2010)
Adsorption of water to fractal dust grains during accretion has been proposed as a possible source of water for rocky planets. We have used computer simulations to study the feasibility of chemisorption onto forsterite dust grains by investigating the adsorption of dissociated water to stoichiometric and defective surfaces. Defects were modeled using steps, corner sites and vacancies on different forsterite surfaces. Our results show that water dissociation is expected on the stoichiometric (100) surface but not on the stoichiometric (010) surface. However, the energies released by dissociative adsorption at steps and corners indicate that the energetic barrier to chemisorption on the (010) surface would be favorable if these features were present. Steps and corners on all surfaces studied produced Mg sites that have low coordination and thus were highly reactive, favoring the dissociation of water. Terrace size between the steps was shown to have a limited effect on the final energies, although smaller terraces created more reactive Mg sites at corners. A simple Langmuir model was used with the energetic data from our simulations to examine the effectiveness of water adsorption at temperature and pressure conditions applicable to the accretion disk. The findings of this study suggest that water would be strongly chemisorbed at fractal forsterite surfaces even at low partial pressures suggesting that water could be retained during planetary accretion. © 2010 Elsevier B.V.